Taxpayer Compliance from the Perspective of Slippery Slope Theory: An Experimental Study - I Nyoman Putra Yasa; I Putu Hendra Martadinata (Jurnal Akuntansi dan Keuangan, 2019)
The aims of this research is to do relevance on taxpayer compliance attitude based on slippery slope theory. The method used in this research is an experimental method with 63 taxpayers as the samples. The result of this research found that taxpayer trust level on tax authority has a positive and significant influence on taxpayer willingness to pay their tax, while tax authority’s power in watching over taxation process does not affect voluntary taxpayer compliance in paying tax. The highest voluntary taxpayer compliance rate is shown by the taxpayer with high trust in tax authority and has strong tax authority. On the other hand, the lowest voluntary taxpayer compliance rate is shown by the taxpayer with low trust on tax authority and have weak tax authority. In summary, this research supported the slippery slope theory and is hoped to be able to strengthen the relevance of slippery slope theory in explaining taxpayer compliance attitude.